Technological Factors that Affect Female Learners in English Translation Studies in Jazan University - Dr. Abdulmajeed Abdulqadir Saeed Alhanash (Taez University, 2023)
There are serious factors, which affect the female learners in translation studies in Jazan University, University College of Addayer. This paper explores those factors as well as how students use the technological applications in translation. The importance of this study arises from the fast developments in translation technological devices in addition to the sensitive issue it highlights. The study suggests that there are technological and personal factors affect the female learners of translation in Jazan University. What are those factors? Are they in need for training in using technological devices for translation? This study uses a descriptive and analytical approach with data collected from different resources. A questionnaire is used as the study instrument and SPSS tool is used for statistical analysis. The study sample is 50 female students from University College of Addayer, Jazan University. The study concludes that the negative dimensions affecting them are classified personally, technologically, and the lack of training. Recommendations are organized and they have a great deal of significance.